Attenuation of sympathetic baroreflex sensitivity during the onset of acute mental stress in humans - Durocher, John J. (American Physiological Society, 2011)
Mental stress consistently induces a pressor response that is often accompanied by a paradoxical increase of muscle sympathetic nerve activity (MSNA). The purpose of the present study was to evaluate sympathetic baroreflex sensitivity (BRS) by examining the relations between spontaneous fluctuations of diastolic arterial pressure (DAP) and MSNA. We hypothesized that sympathetic BRS would be attenuated during mental stress. DAP and MSNA were recorded during 5 min of supine baseline, 5 min of mental stress, and 5 min of recovery in 32 young healthy adults. Burst incidence and area were determined for each cardiac cycle and placed into 3-mmHg DAP bins; the slopes between DAP and MSNA provided an index of sympathetic BRS. Correlations between DAP and MSNA were strong (>0.5) during baseline in 31 of 32 subjects, but we evaluated the change in slope only for those subjects maintaining a strong correlation during mental stress (16 subjects). During baseline, the relation between DAP and MSNA was negative when expressed as either burst incidence [slope = −1.95 ± 0.18 bursts·(100 beats)(−1)·mmHg(−1); r = −0.86 ± 0.03] or total MSNA [slope = −438 ± 91 units·(beat)(−1) mmHg(−1); r = −0.76 ± 0.06]. During mental stress, the slope between burst incidence and DAP was significantly reduced [slope = −1.14 ± 0.12 bursts·(100 beats)(−1)·mmHg(−1); r = −0.72 ± 0.03; P < 0.01], indicating attenuation of sympathetic BRS. A more detailed analysis revealed an attenuation of sympathetic BRS during the first 2 min of mental stress (P < 0.01) but no change during the final 3 min of mental stress (P = 0.25). The present study demonstrates that acute mental stress attenuates sympathetic BRS, which may partially contribute to sympathoexcitation during the mental stress-pressor response. However, this attenuation appears to be isolated to the onset of mental stress. Moreover, variable MSNA responses to mental stress do not appear to be directly related to sympathetic BRS.